Dimensions of belief about miraculous healing - Village, Andrew (Mental health, religion & culture, 2005)
Belief in divine intervention in illness or healing is related to religious belief in general (Furnham, A. (1994). Explaining health and illness: Lay beliefs on the nature of health.Personality and Individual Differences, 17, 455-466; Mansfield, C. J., Mitchell, J., & King, D. E. (2002). The doctor as God's mechanic? Beliefs in the Southeastern United States. Social Science and Medicine, 54, 399-409; Mitchell, J., & Weatherly, D. (2000). Beyond church attendance: Religiosity and mental health among rural older adults. Journal of Cross-Cultural Gerontology, 15, 37-54). There has been little investigation of the nature of such belief among committed churchgoers and, in particular, whether or not belief in miraculous healing is a single or multi-dimensional construct. Scales measuring beliefs about miraculous healing were developed using a sample of 404 Anglicans drawn from a variety of traditions within the Church of England. Participants were asked to respond to various hypothetical scenarios such as a claim that prayer healed cancer, a claim of healing by Spiritualists and a failure to cure someone who had been prayed with for healing. Item scores were subject to an exploratory factor analysis to determine if belief about miraculous healing was multi- or uni-dimensional. Belief in miraculous healing showed at least four dimensions: (1) the possibility of such healing today; (2) the exclusivity of Christian faith healing; (3) the sovereignty of God over illness; and (4) the role of humans in the process. Scores on these dimensions were positively correlated with each other and with measures of conservative Christian belief. Beliefs about healing were strongly correlated with charismatic practice and less strongly to age, education, church attendance and church tradition. Beliefs about miraculous healing among regular churchgoers were complex and varied considerably, even within a single Christian denomination. Simple measures of religiosity and belief do not always adequately describe Christian beliefs about divine intervention in healing.